2D Nb4N5 Nanosheets Synthesized by a Template Method. Issue 10 (15th April 2020) - Su, Yuyu; Wang, Lifeng; Liu, Dan; Zhang, Liangzhu; Wang, Jiemin; Chen, Cheng; Yang, Guoliang; Razal, Joselito; Lei, Weiwei
Abstract: Niobium nitrides possess superconductivity and stable chemical stability, which render them desirable candidates for energy storage. Therefore, they deserve exploration for potential energy storage applications. Here we report on the synthesis of 2D Nb4 N5 nanosheets by ammonization of NbS2 nanosheets as templates at 700 °C. The obtained 2D Nb4 N5 nanosheets retain their hexagon shape and display a porous structure with a pore size of 3.716 nm. These 2D Nb4 N5 nanosheets exhibit capacitor behavior as electrode materials for energy storage. This study opens a new avenue in synthesizing 2D materials based on 2D templates. Abstract : A new approach was explored to synthesize Nb4 N5 nanosheets by a template method. First, NbS2 nanosheets were fabricated by chemical vapor deposition method. Then Nb4 N5 nanosheets were synthesized by ammonization of NbS2 nanosheets in the NH3 atmosphere at 700 °C. Nb4 N5 nanosheets show capacitor behavior as electrode materials for energy storage.